Bridging the Gap Between Degree Programme Curricula and Employability Through Implementation of Work-related Learning - Hills, J. M.; Robertson, G.; Walker, R.; Adey, M. A.; Nixon, I. (Teaching in higher education, 2003)
This article investigates the gap between employers' requirements of graduates and the skills which graduates are furnished with through degree programmes in the higher education (HE) sector in the UK. A survey of 88 subject review reports prepared by the Quality Assurance Agency (QAA) for environmentally related units in the UK showed little emphasis on employability issues. Surveys of first destination statistics of a cohort of graduates from two biological degrees and from national data showed that a significant proportion of graduates were in non-science-based activities. The non-knowledge-based learning outcomes from one degree were investigated, and showed that employability aspects were partially covered in the programme, but were not always associated with secure assessments. The concept of work-related learning is defined and a conceptual framework for HE practitioners is presented that could be used when designing curricula to better map programme learning outcomes onto graduate employment.